Molecular cloning and characterisation of a novel GABAB-related G-protein coupled receptor - Calver, A.R; Michalovich, D; Testa, T.T; Robbins, M.J; Jaillard, C; Hill, J; Szekeres, P.G; Charles, K.J; Jourdain, S; Holbrook, J.D; Boyfield, I; Patel, N; et al. (Brain research. Molecular brain research., 2003)
Using a homology-based bioinformatics approach we have analysed human genomic sequence and identified the human and rodent orthologues of a novel putative seven transmembrane G protein coupled receptor, termed GABA(BL). The amino acid sequence homology of these cDNAs compared to GABA(B1) and GABA(B2) led us to postulate that GABA(BL) was a putative novel GABA(B) receptor subunit. The C-terminal sequence of GABA(BL) contained a putative coiled-coil domain, di-leucine and several RXR(R) ER retention motifs, all of which have been shown to be critical in GABA(B) receptor subunit function. In addition, the distribution of GABA(BL) in the central nervous system was reminiscent of that of the other known GABA(B) subunits. However, we were unable to detect receptor function in response to any GABA(B) ligands when GABA(BL) was expressed in isolation or in the presence of either GABA(B1) or GABA(B2). Therefore, if GABA(BL) is indeed a GABA(B) receptor subunit, its partner is a potentially novel receptor subunit or chaperone protein which has yet to be identified.